Disability rights and religious liberty in education : the story behind Zobrest v. Catalina Foothills School District - Dierenfield, Bruce J., 1951-; Gerber, David A., 1944- (Disability histories (Series), 2020)
"This book project analyzes the social context of, and the judicial rulings in the case of, Zobrest v. Catalina Foothills School District (1993)--a lawsuit with considerable significance for disability and church-state jurisprudence. The question brought before the U.S. Supreme Court by the parents of James Zobrest, a resident of Arizona who is profoundly hearing impaired, was whether James might continue to receive tax-supported sign-language interpretation when, in the absence of public high schools in his area, he moved from a public middle school to Salpointe Catholic High School. When local school officials denied the Zobrests' request on the ground that compliance with it would have the "primary effect of promoting religion," the Zobrests hired a sign-language interpreter at crippling personal expense and also filed suit against the school district, arguing that its opposition to their funding request violated both the free exercise clause of the First Amendment to choose for reasons of faith to send their son to a Catholic high school and the recently passed Individuals with Disabilities Education Act (IDEA), which required states to facilitate the education of children with disabilities"--